MENINGKATKAN KENYAMANAN MASJIDDI DUSUN KARANG PANDAN DAN KARANG BULU DENGAN KONSEP 5R - Siti Hapsah Isfardiyana (UII, 2014)
The mosque became a meeting place with the public, complaining of the problem,the strategy of war, impose sentences, in addition to the main learning place for worshippraying five times,Friday prayers and feast. There is a crowded mosque attended by thecongregation but not least arguably even many mosques were abandoned by thecongregation. Or ethereal many residents were less enthusiastic congregation at themosque. When viewing the irregularity, which is perceived inconvenience. It is certainlyvery disturbing concentration in worship. When an irregularity is turned into a habit,then it can affect the culture. The solution to this irregularity is to implement 5Sconcept. Mosque at Karang Pandan and Karang Bulu have problems in terms ofcleanliness.With 5R applied cleanliness or the sanctity of the mosque are expected toincrease so comfortable congregation in the mosque.